ChemInform Abstract: One‐Pot Multiple Lithiation Processes of Fused Heterocycles. Issue 15 (April 2015) - Jasselin‐Hinschberger, Adeline; Comoy, Corinne; Fort, Yves
Abstract: A highly efficient process which includes successive regioselective lithiation/electrophilic trapping is evaluated and applied to the heterocyclic substrate (I).